Psoriasis and menopause Part I. Impact of psoriasis on quality of life in women in peri- and postmenopausal age - Makara-Studzińska, Marta; Pietrzak, Aldona; Sosnowska, Katarzyna; Kowalczyk, Karolina; Wawrzycki, Bartłomiej; Paszkowski, Tomasz; Chodorowska, Grażyna (Menopause Review/Przegląd Menopauzalny, 2012)
This article is a review of medical literature on the effects of chronic skin disease that is psoriasis on the quality of life in women in peri- and postmenopausal age. In studies on this issue there is a growing literature about the existence of the relationship between the severity of skin lesions and mental state of women during menopause. Authors emphasize the legitimacy of a holistic approach to the patient, taking into account their needs at both the biological and psychological levels. All these issues seem to be vital for improving the quality of life in perimenopausal women with co-occurring psoriasis.